FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) - Laurensia, Lia; Mustikawati, Intan Silviana (Universitas Esa Unggul, 2020)
One of the National Medium Term Development Plan 2015 – 2019 indicator is to increase active acceptors of long-term contraceptive method. In Cengkareng subdistrict community health centre, the proportion of long-term contraceptive method are low (4,6%). The purposed of this research is to analyzed the factors associated preference of long-term contraceptive method among women contraception acceptors in Cengkareng subdistrict community health centre. This research was an descriptive kuantitative with case control approach. The population were all women of contraception acceptors in Cengkareng subdistrict community health centre. The sample were 85 respondent for cases (total sampling) and 85 respondent for control (simple random sampling). This research used quisionaire instrument and analyzed used chi square test (α = 0,05). The result showed that variables which associated preference of long-term contraceptive method are educational level (sig = 0,001), knowledge (sig = 0,006), and support of spouse (sig = 0,005. As for age (sig = 0,177), number of children (sig = 0,490) and cost of contraception used (sig = 0,368). The suggestion for Cengkareng subdistrict community health centre are increase the service of give information for the citizen about long – term contraceptive method. Keywords : Long-term contraceptive method, Family planning, contraceptives